Systematic approach for migrating to a structured reporting context based on free-text reports and the DICOM Structured Reporting guidelines - Beckauser, Eduardo; Petrolini, Vinicius Andreoli; Savaris, Alexandre; Wangenheim, Aldo von; Krechel, Dirk (Anais do Simpósio Brasileiro de Computação Aplicada à Saúde (SBCAS); 2019: Anais do XIX Simpósio Brasileiro de Computação Aplicada à SaúdeDO - 10.5753/sbcas.2019.6245, 2019)
Even with the many advantages of adopting a structured reporting system, there is little convention on how to disseminate this routine into the report environment. This work proposes a systematic approach to migrate a system routine from free-text reports to structured reports, focusing on the DI- COM Structured Reporting guidelines. We evaluated this proposal by creating a reporting module in the context of a telemedicine system, and performing case study covering ultrasonography reports. Using the AdEQUATE model, the eval- uation showed a high user perception from the system, directly reflecting the quality of our proposal. The results are a set of defined premises and steps that turns a telemedicine system into a complete structured reporting environment.